Centralni venski pristop k veni subklaviji - Zver, Samo (Medicinski razgledi, 1996)
Central venous catether is for many years accompanist of intensive treatment. In the article are described supraclavicular subclavian-vein approach by Yoffa and medial infraclavicular approach. Both are among the commonest subclavian-vein catheterization techniques in use. Also are described the most commonest complications during the procedure and after, during the use of central venous catheter.
Keywords: interna medicina